2022
DOI: 10.1155/2022/9584507
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil Transcriptional Deregulation by the Periodontal Pathogen Fusobacterium nucleatum in Gastric Cancer: A Bioinformatic Study

Abstract: Background. Infection with the periodontal pathogen Fusobacterium nucleatum (F. nucleatum) has been associated with gastric cancer. The present study is aimed at uncovering the putative biological mechanisms underlying effects of F. nucleatum–mediated neutrophil transcriptional deregulation in gastric cancer. Materials and Methods. A gene expression dataset pertaining to F. nucleatum-infected human neutrophils was utilized to identify differentially expressed genes (DEGs) using the GEO2R tool. Candidate genes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…21, [135][136][137] Furthermore, Fusobacterium can chemoattract neutrophils via release of SCFA and can also modulate neutrophils and endothelial cell functions in vitro. [138][139][140][141][142] Interestingly, we observed that patients with low levels of Fusobacterium within the tumour tissue had shorter overall survival, consistent to previous reports in HNSC. 45,60,143 In contrast, opposite findings have been reported for colorectal, gastric and oesophageal cancers, suggesting that Fusobacterium may have a different role in HNSC.…”
Section: Evaluation Of Microbiota Abundance With Clinical Features An...supporting
confidence: 91%
“…21, [135][136][137] Furthermore, Fusobacterium can chemoattract neutrophils via release of SCFA and can also modulate neutrophils and endothelial cell functions in vitro. [138][139][140][141][142] Interestingly, we observed that patients with low levels of Fusobacterium within the tumour tissue had shorter overall survival, consistent to previous reports in HNSC. 45,60,143 In contrast, opposite findings have been reported for colorectal, gastric and oesophageal cancers, suggesting that Fusobacterium may have a different role in HNSC.…”
Section: Evaluation Of Microbiota Abundance With Clinical Features An...supporting
confidence: 91%
“…A bioinformatic analysis suggested that neutrophil transcriptional activation induced by F. nucleatum may be implicated in the occurrence of GC through several candidate genes, including DNAJB1, EHD1, IER2, CANX, and PH4B. Functional analysis showed that membrane-bound organelle dysfunction, intracellular trafficking, transcription factors ER71 and Sp1, and miR580 and miR155 were other candidate mechanisms ( Zhou et al, 2022 ). The metabolic function analysis showed that F. nucleatum -positive GC tissues were significantly enriched in the biosynthesis of lysine, peptidoglycan, and tRNA metabolic functions ( Nie et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“… 68 Another study proposed that F. nucleatum -induced transcriptional activation in neutrophils might be linked to gastric carcinogenesis through various candidate genes, with suggested functional mechanisms including organelle dysfunction and intracellular transport dysregulation. 69 Intriguingly, the impact of F. nucleatum appears to differ among GC subtypes, with F. nucleatum -positive patients displaying a poorer prognosis in the context of Lauren diffuse GC, while no substantial difference was noted in intestinal GC patients. This observation hints at the prospect that F. nucleatum may exert disparate modes of action within the domain of Lauren diffuse GC, 67 although further research is required to elucidate the precise mechanisms involved.…”
Section: F Nucleatum and Tumorigenesis Tumor Metastasismentioning
confidence: 98%